HUBUNGAN ETIKA PELAYANAN PENDIDIKAN KRISTEN DENGAN PENDIDIKAN INDONESIA - Christie Kusnandar (Journal of Accounting and Management Innovation, 2021)
Serving is a noble calling that should be done by anyone, including in the world of education. A person's character will appear when in his daily life he is able to realize the values of service to God and others. For this reason, the world of education as an institution that produces the next generation of the nation is asked to carry out this calling through noble values that are instilled in students. Character building for students is formed through learning ethics which is related to the concept of serving. As a whole, understanding the world of education is not free from the concept of serving, which includes educating services for students and services from students for the society. For this reason, both educators and students must have a right and properly understanding in serving through the implementation of a holistic and integrated service ethic. (As a comparison, this study is carried out in Christian scientific studies, specifically the ethics of Christ's ministry in the Book of Isaiah).Keywords: Ethics, Serving, Education, the Book of Isaiah.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}.MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;}div.WordSection1 {page:WordSection1;}